Analysis of Traffic Noise Pollution at School Area that Located in Gemencheh Town, Negeri Sembilan - Murally, Thevhan; Daud, Zawawi (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Humans have caused a great deal of tremendous progress in recent times. However, in order to accomplish progress, one of the challenges generated by humans was Road Traffic Noise, which was caused by the unavoidable arrival of vehicles on the road. This research study was done primarily in three school areas: SMK Dato Mohd Taha, SJK(C) Sin Min, and SK Datuk Abdullah, all of which are located in Gemencheh town. The sound level meter (SW-524) was utilized for the measurement. For three days, each school was monitored (07:30-08:30) in the morning and (12:30-1:30) in the afternoon for one-hour data traffic noise collection: Day 1 (Sunday), Day 2 (Monday), and Day 3 (Tuesday) (Tuesday). In addition, a questionnaire survey was distributed to school pupils in order to determine their level of awareness. . According to the data studied traffic noise, SMK Dato Mohd Taha had the highest Leq 92.11dBa, TNI 139.5dBa, and Lnp value of 70.90dBa. In addition, SJK(C) Sin Min recorded 29.1dBa. Meanwhile, SK Datuk Abdullah does not violate the DOE’s real noise limit. DOE’s actual noise limit for Leq was 60dBa, TNI was 74dBa, and Lnp was 88dBa. According to the data acquired, the Leq, TNI, and Lnp surpass the DOE Malaysia’s maximum noise limit guidelines. The largest number of respondents (schoolchildren) who replied "Yes" in the questionnaire survey was 51 for SMK Dato Mohd Taha. In comparison to SK Datuk Abdullah, there was just one "Yes" response. This depicts the SMK Dato Mohd Taha disastrous position. This depicts the disastrous scenario of the SMK Dato Mohd Taha traffic noise since its road was the main road between Tampin and Gemas. SK Datuk Abdullah respondents also responded "No" with 99 respondents.